Mediation of transfer motivation on the relationship between trainee characteristics and transfer of training : evidence from educational sector in Nigeria - Wasilu, Suleiman; Mudiyanselage, Saman Dassanayake; Abang Ekhsan, Abang Othman (Taylor & Francis Ltd., 2018)
This paper is ambitious of investigating the mediating role of transfer motivation on trainee characteristics in transferring training on the population of Nigerian teachers. An aggregate of 1,000 copies of the questionnaire was distributed to the respondents in an Education Board in Nigeria. Totally, 605 copies of the questionnaire were finally retained for analysis. Smart-PLS’s measurement model, structural model and Sobel test were the techniques employed to assess and evaluate the statistical significance of relevant path coefficients. The findings showed that the extent to which employees are engrossed in organizational commitment and fully involved in their jobs would drive them to be desirous in making persistent and intense efforts towards utilizing skills and knowledge learned in the work settings. Also, the findings of this study highlighted that transfer motivation is a fundamental element in the transfer of training processes.